Role of three tick species in the maintenance and transmission of Severe Fever with Thrombocytopenia Syndrome Virus. - Yuan-Yuan Hu; Lu Zhuang; Kun Liu; Yi Sun; Ke Dai; Xiao-Ai Zhang; Pan-He Zhang; Zhi-Chun Feng; Hao Li; Wei Liu (Public Library of Science (PLoS), 2020)
Severe fever with thrombocytopenia syndrome virus (SFTSV) is a novel phlebovirus in the Bunyaviridae family, causing SFTS with high mortality rate. Haemaphysalis longicornis ticks has been demonstrated as a competent vector of SFTSV by experimental transmission study and field study. However, there has been query whether other tick species that infest human beings in the SFTS endemic regions are capable of transmitting the pathogen. Here by performing experimental transmission study, we compared the capable of transmitting SFTSV among Ixodes sinensis, Ixodes persulcatus and Dermacentor silvarum ticks. The transovarial transmission was seen in the I. sinensis ticks with a rate of 40%, but neither in I. persulcatus nor in D. silvarum ticks. I. sinensis ticks also have the ability to transmit SFTSV horizontally to uninfected mice at 7 days after feeding, but not for I. persalcatus or D. silvarum ticks. In the transstadial transmission of I. persulcatus and D. silvarum ticks, I. persulcatus ticks were tested negative from larvae to adults. But the D. silvarum ticks were tested positive from larvae to nymphs, with the positive rate of 100% (10/10) for engorged larval ticks and 81.25% (13/16) for molted nymphs. However, the mice bitten by SFTSV-infected D. silvarum nymphs were negative for SFTSV detection. Therefore, there is not enough evidence to prove the transstadial transmission of SFTSV in I. persalcatus and D. silvarum ticks.